LEADERSHIP MEMBER EXCHANGE (LMX) MODEL, WORK DISCIPLINE AND ITS COMPENSATION EFFECT ON EMPLOYEE ORGANIZATIONAL ENVIRONMENT PT. FIF GROUP SURABAYA - Kuswandi Kuswandi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research aims to determine the Leadership Member Exchange (LMX) Model which has implications for discipline and compensation in the PT FIF Group Surabaya Organization. The sampling technique used in this study is Technique Nonprobability Sampling). Furthermore, researchers took the population of all employees a number 50 respondents. The sample in the study of all employees PT. FIF Group as much 50 respondents. Data collection techniques are interviews, observations and questionnaires. Methods of data analysis using Multiple Linear Regression. The findings of this study indicate that with the LMX model Leadership is able to create innovative and unique working relationships in the organization according to competencies according to their field of work in the organization at PT. FIF Group with a t value of 4.026 and a significance level of 0.000, on the implications of work discipline there is a partially significant relationship with the organization with a t value of 2.389 and a significance level of 0.021 as well as compensation having partial significant implications on the PT organization. FIF Group with a t value of 2.165 and a significance level of 0.036. The Leadership Member Exchange (LMX) model has implications for Discipline, Compensation has implications for the organization, the findings in this study are the LMX model for organizations that were previously unhealthy to live according to information, technology and communication developments, a linear communication model. Simultaneously there is a significant impact on the organizational environment of PT employees. FIF Group with a calculated f value (22.423) > f table (2.70) with a significance of 0.000. The value of R square (R2) is 0.594, indicating that the relationship between the three research variables and the dependent variable is 59.4%. Meanwhile, the remaining 40.6% was suggested by the work life balance variable, rewards which were not included in the research.